Quality function deployment modelling to enhance industrialised building system adoption in housing projects - Haron, Nuzul Azam; Abdul Rahman, Hamzah; Chen, Wang; Wood, Lincoln C. (Routledge, 2015)
A quality tool in achieving the required quality and customer satisfaction of the industrialised building system (IBS) is needed. Aiming to develop a general quality function deployment (QFD) model to enhance the adoption of IBS in housing projects, two sets of structured questionnaires were designed, where the first set was for IBS house occupiers and the second set for construction stakeholders. Frequency distribution, arithmetic measure, gap analysis, Pareto analysis, and QFD application were employed to identify the customer satisfaction factors and the IBS adoption strategies. A general QFD model was developed based on the ‘quality’ matrix (Q-Matrix), ‘function’ matrix (F-Matrix), and a combination of ‘quality’ matrix plus ‘function’ matrix (QF-Matrix) derived from this study. Customer satisfaction with IBS products could enhance the demand for this kind of building automation system, thus the model could be used more objectively in developing, designing, and managing IBS in the global construction industry, especially in the current economic recession and recovery phase.